2010
DOI: 10.1124/jpet.110.167510
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cytochrome P450 Epoxygenases Prevents Development of Hypertension in Spontaneously Hypertensive Rats by Enhancing Atrial Natriuretic Peptide

Abstract: Cytochrome P450 (P450)-derived epoxyeicosatrienoic acids (EETs) exert well recognized vasodilatory, diuretic, and tubular fluid-electrolyte transport actions that are predictive of a hypotensive effect. The study sought to determine the improvement of hypertension and cardiac function by overexpressing P450 epoxygenases in vivo. Long-term expression of CYP102 F87V or CYP2J2 in spontaneously hypertensive rats (SHR) was mediated by using a type 8 recombinant adeno-associated virus (rAAV8) vector. Hemodynamics wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…In vivo experiments showed that CYP2J2 overexpression attenuates production of VCAM, E-selectin, IL-1 ␤ , and IL-6 while enhancing production of the anti-infl ammatory cytokine IL-10. In addition, CYP2J2 gene delivery via intravenous injection signifi cantly increased CYP2J2 expression in vivo in most organs, mainly aorta, heart, liver, and kidney ( 3,5,6,36,37 ), which may also explain some effects of heart protection. These results support the view that CYP2J2-derived EETs protect the heart via their antiinfl ammatory, antiapoptotic, and prosurvival effects.…”
Section: Improvement Of Hemodynamics and Systemic Infl Ammation In Tnmentioning
confidence: 99%
“…In vivo experiments showed that CYP2J2 overexpression attenuates production of VCAM, E-selectin, IL-1 ␤ , and IL-6 while enhancing production of the anti-infl ammatory cytokine IL-10. In addition, CYP2J2 gene delivery via intravenous injection signifi cantly increased CYP2J2 expression in vivo in most organs, mainly aorta, heart, liver, and kidney ( 3,5,6,36,37 ), which may also explain some effects of heart protection. These results support the view that CYP2J2-derived EETs protect the heart via their antiinfl ammatory, antiapoptotic, and prosurvival effects.…”
Section: Improvement Of Hemodynamics and Systemic Infl Ammation In Tnmentioning
confidence: 99%
“…In humans, CYP2J2 is highly expressed in cardiac myocytes and the endothelium of coronary arteries where it plays significant roles in cardiovascular diseases and inflammation. [4][5][6][7] This enzyme Abbreviations: CPR, cytochrome P450 reductase; CYP2J2, cytochrome P450 2J2; ND, Nanodiscs; POPC, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine; POPS, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoserine.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that EETs and CYP epoxygenases markedly activate Akt and inhibit cardiac hypertrophy (Xiao et al ., 2010). To further understand this controversial phenomenon, we investigated whether 11,12‐EET‐induced ANP expression was mediated by the activation of Akt in cardiac hypertrophy and whether EETs enhanced the nuclear translocation of Akt.…”
Section: Resultsmentioning
confidence: 99%
“…There are accumulating evidences that EETs (Althurwi et al ., 2013; He et al ., 2015) might also protect against cardiac hypertrophy (Ai et al ., 2009). Overexpression of CYP epoxygenases improved cardiac function in spontaneously hypertensive rats, and these effects may have been mediated, at least in part, by the atrial natriuretic peptide (ANP) activation of the epidermal growth factor (EGF) receptor (Xiao et al ., 2010). However, the detailed molecular mechanisms by which EETs protect against cardiac hypertrophy or heart failure remain unclear.…”
Section: Introductionmentioning
confidence: 99%